Cameron Jamie - Rugoff, Ralph 1957-; Filipovič, Ėlʹvira Grigorʹevna 1934- (Phaidon Press, 2024)
Phaidon and Artspace are pleased to announce a new limited edition of 15 silkscreen prints by acclaimed contemporary artist Cameron Jamie, entitled Pinky Blues, 2024. For more than three decades, Jamie’s groundbreaking work has explored, investigated, and analyzed how the structures of mythology and rituals in popular and vernacular cultures are shaped and shared, and the extent to which they participate in the creation of individuals’ fictional worlds and fictional selves. Pinky Blues nods to these themes with expressive gestural linework and a vibrant interplay of colors that seem to emerge from the depths of the human psyche. Each signed and numbered print comes with a custom portfolio and a special signed hardback edition of Jamie’s new Contemporary Artist Series monograph published by Phaidon
"This volume of Cameron Jamie is published in a limited edition of 15 copies, each with an original print signed by the artist"
Keywords: Jamie, Cameron -- 1969-